Penyuluhan Pengelolaan Botol Bekas Menjadi Pot Bunga Untuk Meningkatkan Kreativitas Dan Kesadaran Siswa di SDN 4 Cakranegara - Ahmad, Nuraihan; Nurmekasari, Nurmekasari (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2024)
Plastic bottle waste is still considered as less useful waste. Plastic bottle waste can be used in various forms of goods that are useful and have selling value. This activity aims to reduce used plastic bottle waste in the school environment into useful items with selling value. The methods used in this research are survey, discussion, and training or practice. The results of this research are that Teaching Assistance (AM) students provide theoretical explanations, and then students are allowed to try making products from used plastic bottles according to the techniques taught and the equipment provided. During manufacturing practice, students are also encouraged to look at each other's work, so they can evaluate their work and at the same time make judgments about the correct work process and results. This research suggests follow-up in the form of training and assistance regarding waste and waste management, especially plastic bottles into products with higher economic value or more useful. Contains outside suggestions for further research.